Perubahan Sosial Ekonomi dan Penggunaan Lahan di Desa Bandar Klippa: Dampak dari Stasiun Kereta Api - Arma Fauziah; Angelo Arevalo Simanullang; Clarissa Oktoferin Sinaga; Muhammad Najuml Fahmi; M. Hayqal Adibya (Inspirasi Dunia: Jurnal Riset Pendidikan dan Bahasa, 2024)
Land use changes can impact society, the government, and the environment in either a beneficial or harmful way. The physical and non-physical components of Bandar Klippa Village underwent a variety of modifications as a result of changes in land usage. This is because a train station is being built in North Sumatra's Percut Sei Tuan District's Bandar Klippa Village. The purpose of this study is to examine how the construction of the Banda Klippa train station has affected land use. In this study, a resident of Bandar Klippa Village was interviewed and field observations were made. The study's findings indicate that Bandar Klippa Village's land use is changing, which has an effect on the neighborhood and its inhabitants in particular.